¿Cómo funciona el derecho de aguas a 3300 m.s.n.m.? - Guevara Gil, Armando (2014)
The authorities in charge of managing our Andean basins work in unimaginable water-powered landscapes from the Peruvian legislator point of view. They should generate and apply peculiar mechanisms. Why? Because the national legislator is traditionally positioned on the coast, a region very different to the Andean highlands and punas. The use of ethnographic evidence coming from a drainage basin in the Central Andes (Mantaro River, Junin) lets me depict in detail how public officers appeal to mechanisms of location, adaptation and regulation in order to adjust the official regulations, to cover the needs of the farming organizations of watering, and to affirm their positions as representatives of the Peruvian government. The consequence is that they exceed and also violate the regulatory channels that control their administrative functions. In this way, they incorporate a new function to their official position, that is, to develop peculiar administrative patterns to process the tightness between the inflexibility of the State Water Right and the demands of recognition and balance that the andean watering organizations propose to the Government.